University Entrance Examinations in Spain: Using the Construct Comparability Approach to Analyze Standards Quality - Veas, Alejandro; Navas, Leandro; Pozo-Rico, Teresa; Miñano, Pablo (Frontiers in Psychology, 2020)
In recent years, important methodological attempts have been made to explore the comparability of examination standards, especially in the context of certifications and university entrance. The present study aimed to explore the use of a construct comparability approach through a comparative analysis of the academic scores on 15 subjects from Spanish University Entrance Examinations in the Valencian Community, with a sample of 22,996 students in the call of June 2018. We employed the Rasch partial credit model as an estimation method, counting each subject as the item of an instrument related to academic achievement. The results confirmed the unidimensionality assumption and the goodness of fit of the model in relation to all subjects, although no discrimination between high and low ability students was detected because of the lack of monotonicity of the score categories. We observed that the level of difficulty of the subjects was appropriate to the students’ ability levels. Important conclusions have been drawn for the improvement of the standard qualification process, and future research directions have been proposed.